Clinical and diagnostic imaging findings in a Bengal tiger (Panthera tigris tigris) with craniocervical artery dissection: a case report - Zadeh, Peyman Mohammad (Slovenian veterinary research, 2024)
This study aims to examine different aspects of Craniocervical Artery Dissections, which resulted in the animal’s death following a sequence of pathological events. Following the physical damage to the female Siberian tiger neck due to the Agonistic behaviour of the male tiger, diagnostic tests such as complete medical examination, Time-of-Flight (TOF) MRA imaging and radiography, as well as sampling for clinical assessment, haematology, microbial culture, and antibiogram was performed, initial treatment was prescribed, and PCR was performed. Unfortunately, the Medical treatment measures were inadequate, and the animal died. Therefore, necropsy, histopathological examination, and immunohistochemistry staining were performed. The results of the microbiological study included the identification of Bergeyella zoohelcum for the first time in this animal species, as well as diagnostic findings; necropsy and histological examinations, including aneurysm, subarachnoid haemorrhage, and ischemic stroke, were provided as well as Horner’s intramural hematoma and rupture of the carotid arteries and internal jugular vein, which has never been described before. Whole-body trauma computed tomography with an adapted scanning protocol for the craniocervical vessels is a safe, fast, and feasible method for detecting vascular injuries. It allows prompt further treatment if necessary. This method could be a part of a broad screening protocol for craniocervical vessels in documented injuries of the head and neck and trauma mechanisms influencing the craniocervical region as well.
Keywords: ischemic stroke; subarachnoid haemorrhage; tiger; transient ischemic attack